SEBT AND YBT DYNAMIC BALANCE TESTS - Mariana CORDUN; Bogdan ROȘU (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae, 2022)
A fundamental role in movement control is given by proprioceptive information from a multitude of mechanoreceptors that are integrated and processed by the human brain. Understanding proprioception and the test method, such as the threshold for detecting passive movement and reproducing joint position, are used to assess proprioception. The origin of the methods, test apparatus and procedures or protocols used in each approach are compared and discussed. Instability of a lower limb joint is a risk factor for these areas. Therefore, the development of proprioception can play an important role in injury prevention. The Star Excursion Balance Test (SEBT) is a dynamic postural control task that has gained notoriety in clinical and research settings, it is able to provide objective measures to differentiate deficiencies and improve dynamic postural control related to lower limb joint injuries. The clinical application of the SEBT led to the development of the Y Balance Test (YBT), both SEBT and YBT involve similar movements that are deemed to measure and challenge dynamic balance.